Fibrinogen and D‐dimer levels elevate in advanced hepatocellular carcinoma: High pretreatment fibrinogen levels predict poor outcomes. Issue 11 (31st January 2017) - Liu, Zhikun; Guo, Haijun; Gao, Feng; Shan, Qiaonan; Li, Jie; Xie, Haiyang; Zhou, Lin; Xu, Xiao; Zheng, Shusen
Abstract : Aim: Plasma fibrinogen and D‐dimer have been reported to predict survival in several types of malignancies. The aim of this study is to investigate their predictive value in patients with hepatocellular carcinoma (HCC). Methods: We retrospectively analyzed plasma fibrinogen and D‐dimer levels from 252 subjects: control ( n = 20), hepatitis ( n = 20), cirrhosis ( n = 20), and HCC ( n = 192) subjects. The clinical involvement and prognostic value of fibrinogen and D‐dimer was analyzed in HCC subjects. To confirm the effects of tumor on hypercoagulability and fibrinolysis, fibrinogen and D‐dimer levels were measured in nude mice following HCC inoculation. Results: Fibrinogen decreased and D‐dimer increased in cirrhosis subjects relative to other groups. In HCC subjects, elevated fibrinogen and D‐dimer levels were significantly associated with adverse tumor features (increased size, stage, and grade) and systemic inflammation. Patients with HCC with either elevated fibrinogen or D‐dimer levels had significantly higher 3‐year tumor recurrence rates (65% vs. 41%, P < 0.001 for fibrinogen; 67% vs. 40%, P = 0.011 for D‐dimer) and significantly lower 3‐year overall survival rates (57% vs. 79%, P < 0.001 for fibrinogen; 56% vs. 80%, P = 0.001 for D‐dimer). After multivariate analysis, elevated fibrinogen levels remained an independent predictor of poor prognosis in HCC patients. Finally, elevated levels of fibrinogen and D‐dimer were confirmed in nude mice following tumor inoculation. Conclusion: The fibrinogen and D‐dimer levels, elevating after carcinogenesis, may serve as simple but effective predictors of adverse tumor profiles and outcomes in HCC.